Analysis of the Levels of Organizational Culture of Academicians in Terms of Some Variables - NACAR, Eyyup (Asian Journal of Education and Training, 2019)
The main purpose of this research is to examine the level of organizational culture of academicians in terms of some variables. The research universe is formed by academicians at Fırat University in the 2018-2019 academic year. The sample of the study is 96 randomly selected academicians from Fırat University Faculty of Education, Faculty of Humanities and Social Sciences and Faculty of Sports Sciences in the 2018-2019 academic year. The Personal Information Form was used in order to determine the demographic information of the subjects participating in the study, in addition, "Organizational Culture Scale" was used that prepared by Ogbonna and Harris (2000) and translated into Turkish by Karadeniz (2010) and developed in the master’s study. The data of the research were determined to be parametric. Therefore, t test and variance analysis (Anova) test was used. Tukey test and LSD test results were used to determine which groups the difference was among the results with significant differences. The error level in the study was taken as p<0.05. As a result of the research, academicians’ organizational culture scale is based on the findings; it was found that there was no statistically significant difference in all sub-dimensions of the title and gender variable. There was a statistically significant difference in faculty, age group and academic study year variables.